Serum HMGB1 as a diagnostic biomarker and mediator of childhood trauma in adolescent depression - Xiang, Jingyue; Qin, Yiqun; Jiang, Ruhong; Wang, Xiaolan; Zhou, Yang; Liu, Jia; Kuang, Li (Frontiers in Psychiatry, 2025)
BackgroundAdolescent depression is a global health challenge with increasing rates and long-term impacts on development. Current diagnostics lack objective biomarkers, relying on subjective assessments. Neuroinflammation, particularly High mobility group box 1 (HMGB1), a systemic inflammation mediator, is implicated in adult depression but not well-studied in adolescents. Childhood trauma, a risk factor for neuroinflammatory dysregulation, has been linked to increased inflammatory markers but not specifically to HMGB1. This study explores serum HMGB1 as a diagnostic biomarker for adolescent depression and its role in exacerbating symptoms through childhood trauma.Methods160 participants, including 80 depressive adolescents and 80 healthy controls, were enrolled. The depressive symptoms of depressive adolescents were evaluated with clinical scale. Serum HMGB1 levels were measured by enzyme-linked immunosorbent assay (ELISA). Correlation analysis, multiple linear regression, and mediation effect analysis were utilized to examine the relationship between serum HMGB1 levels and depressive symptoms severity.ResultsCompared with the control group, serum HMGB1 levels (t = -18.48, P <0.001) was increased in depressive adolescents. Correlation analysis showed that serum HMGB1 levels in depressive adolescents were positively correlated with 17-item Hamilton Depression Rating Scale (HAMD-17) scores and Childhood Trauma Questionnaire (CTQ) scores. Multiple linear regression analysis showed that serum HMGB1 levels can independently predict HAMD-17 scores for depressive adolescents. HMGB1 demonstrated high diagnostic accuracy (AUC = 0.984) and significantly mediated depressive symptoms through childhood trauma (indirect effect = 0.0028, 95% CI: 0.0008-0.0058).ConclusionSerum HMGB1 levels are potential markers of depression, and childhood trauma partially mediates the relationship between HMGB1 and depressive symptoms severity.